MicroRNA-381-3p Functions as a Dual Suppressor of Apoptosis and Necroptosis and Promotes Proliferation of Renal Cancer Cells - Zhao, Cong; Zhou, Yifei; Ran, Qiao; Yao, Ying; Zhang, Haoran; Ju, Jie; Yang, Tao; Zhang, Wei; Yu, Xiaoliang; He, Sudan (Frontiers in Cell and Developmental Biology, 2020)
Renal cell carcinoma (RCC) is the most common type of kidney cancer. It has a poor prognosis, with approximately 20-30% of patients developing recurrent and/or metastatic diseases that is relatively high resistant to conventional therapy. Resisting cell death is a hallmark of cancer cells. Apoptosis is a form of programmed cell death mediated by the activation of caspases. Necroptosis is a form of regulated necrosis that relies on the activation of receptor-interacting protein kinase 1 (RIPK1), RIPK3 and mixed lineage kinase domain-like protein (MLKL), the substrate of RIPK3. Cancer cells often display apoptosis resistance via upregulation of anti-apoptotic genes and defective necroptosis due to the epigenetic silence of Ripk3. MicroRNAs (miRNAs) are non-coding small RNAs that are involved in numerous biological processes including cell proliferation, differentiation and death. In this study, we screened a set of ~120 miRNAs for apoptosis-regulating miRNAs and identified miR-381-3p as a suppressor of TNF-induced apoptosis in various cancer cells. Ectopic expression of miR-381-3p inhibits the activation of caspase-8 and caspase-3. The expression level of miR-381-3p inversely correlates with the sensitivity of cancer cells to TNF-induced apoptosis. Moreover, we found that overexpression of miR-381-3p blocks TNF-induced necroptosis by inhibiting the activation of RIPK3 and MLKL. Of note, Kaplan-Meier Plotter analysis demonstrates that papillary RCC patients with high miR-381-3p expression have a lower overall survival than those with low expression level of miR-381-3p. Importantly, miR-381-3p overexpression promotes colony formation in human renal cancer cells. Thus, miR-381-3p acts as an oncogenic miRNA that counteracts both apoptotic and necroptotic signaling pathways. Our findings highlight miR-381-3p as a biomarker for predicting sensitivity to apoptosis and necroptosis, and as a possible therapeutic target for RCC.